The Context Of Knowledge In Organizations From Resource Based Theory To Knowledge Based Theory: A Conceptual Review - Muhammad Ihsan Jambak (Universitas Sriwijaya, 2015)
Abstract Nowadays, organizations in order to increase their competitive advantages, they put more focus on managing the intangible assets rather than the tangible assets including the intellectual capital. Since the value of intellectual capital is resided in the talented human capital, therefore the talent management is commonly used for human resource management. The root of talent management is came from the Resource Based Theory (RBT) that treats the human capital as static assets that only need to be attracted, developed, updated, deployed and retained. In contrast, this paper appreciates the talent as an individual tacit knowledge that more than the said above, it can be created, captured and transferred, which is aligned with the Knowledge Based Theory (KBT). Keywords: Human Resource Management, Human Capital, Knowledge Capital, Talent Management, Knowledge Management Â Abstrak Dewasa ini, dalam rangka meningkatkan keunggulan kompetitif organisasi-organisasi bisnis lebih menempatkan perhatian mereka pada pengelolaan aset tidak berwujud daripada aset berwujud, termasuk di dalamnya modal intelektual. Karena nilai modal intelektual terletak pada modal manusia bertalenta, maka talent management digunakan dalam manajemen sumberdaya manusia.Â Talent management berakar pada Resource Based Theory (RBT) yang memperlakukan sumberdaya manusia sebagai aset statis yang hanya perlu untuk ditarik, dikembangkan, diperbarui, digunakan, dan dipertahankan.Â Sebaliknya, tulisan ini mengapresiasi talenta sebagai pengetahuan tacit individu lebih daripada sebagaimana disebut diatas, bahwa pengetahuan tacit individu dapat diciptakan, dapat ditangkap dari tempat lain, dan dapat ditransfer ke tempat lain, yang mana hal ini selaras dengan Knowledge Based Theory (KBT) Kata kunci: Manajemen Sumberdaya Manusia, Modal Manusia, Modal Pengetahuan, Manajemen Talenta, Manajemen Pengetahuan